2022
DOI: 10.20944/preprints202209.0115.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Profound Impact of Decline in N-Acetylgalactosamine-4-Sulfatase (Arylsulfatase B) on Molecular Pathophysiology and Human Diseases

Abstract: The enzyme N-acetylgalactosamine-4-sulfatase (Arylsulfatase B; ARSB) was originally identified as a lysosomal enzyme which was deficient in Mucopolysaccharidosis VI (MPS VI; Maroteaux-Lamy Syndrome). Newly directed attention to the impact of ARSB in human pathobiology indicates a broader, more pervasive effect, encompassing roles as a tumor suppressor, transcriptional mediator, redox switch, and regulator of intracellular and extracellular-cell signaling. By controlling the degradation of chondroitin 4-sulfate… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 142 publications
(366 reference statements)
0
3
0
Order By: Relevance
“…Other work has shown that when ARSB is inhibited and 4-sulfation sustained, SHP2 binding to chondroitin 4-sulfate is increased, leading to reduced SHP2 activity and sustained phosphorylation of ERK1,2, JNK, and p38 [14,53-56]. The impact of phospho-38-MAPK on N-terminal Rb phosphorylation, Rb-E2F1 binding, and suppression of ARSB promoter activation, may be part of a loop, in which p38 phosphorylation is sustained, due to enhanced chondroitin 4-sulfate-SHP2 binding which follows decline in ARSB and increased chondroitin 4-sulfation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Other work has shown that when ARSB is inhibited and 4-sulfation sustained, SHP2 binding to chondroitin 4-sulfate is increased, leading to reduced SHP2 activity and sustained phosphorylation of ERK1,2, JNK, and p38 [14,53-56]. The impact of phospho-38-MAPK on N-terminal Rb phosphorylation, Rb-E2F1 binding, and suppression of ARSB promoter activation, may be part of a loop, in which p38 phosphorylation is sustained, due to enhanced chondroitin 4-sulfate-SHP2 binding which follows decline in ARSB and increased chondroitin 4-sulfation.…”
Section: Discussionmentioning
confidence: 99%
“…Arylsulfatase B (ARSB) activity measurements were performed using a fluorometric assay, following a standard protocol with 20 μl of homogenate and 80 μl of assay buffer (Na acetate 50mM with barium acetate 20mM, pH 5.6) with 100μl of substrate (5 mM 4-MUS in assay buffer) in a black microplate, as previously detailed [14].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation